Application complex computer-aided design of highways credo in educational process - Бєлятинський, А.О.; Чешуйко, В.М. (Proceedings of National Aviation University, 2006)
The application of the automated program complex CREDO in course and degree designing of autoroads is considered in a scientific process of National Aviation University.